Contributions of risk factors and medical care to cardiovascular mortality trends - Ezzati, Majid; Obermeyer, Ziad; Tzoulaki, Ioanna; Mayosi, Bongani M.; Elliott, Paul; Leon, David A. (Nature reviews cardiology, 2015)
Key Points Death rates from ischaemic heart disease (IHD), stroke, and other cardiovascular diseases (CVDs) are decreasing in high-income and many Latin American countries, and this trend shows no signs of slowing Declines in some behavioural risk factors, including smoking, and physiological risk factors, such as blood pressure and serum cholesterol, are likely to have helped to reduce CVDs By contrast, the nearly universal increase in adiposity seems not to have modified the long-term declining trend in CVD mortality, although it might have had some slowing effect Improved medical care, including effective treatment of physiological risk factors, diagnosis, treatment of acute CVDs, and post-hospital care, has also contributed to declining CVD events and mortality Measured risk factor and treatment variables, while important, explain neither why the decline began when it did nor many of the similarities and differences between countries or between men and women Substantial fluctuations in CVDs, and in alcohol intake, in former communist countries of Europe have followed times of massive political and social changes since the early 1990s Cardiovascular disease (CVD) remains a leading cause of death worldwide, but age-standardized CVD death rates are decreasing steadily. In this Review, Ezzati and colleagues use the available epidemiological data to examine regional and global changes in CVD mortality, as well as trends in smoking, alcohol consumption, diet, physiological risk factors, and improvements in medical care that might underlie these changes. Ischaemic heart disease, stroke, and other cardiovascular diseases (CVDs) lead to 17.5 million deaths worldwide per year. Taking into account population ageing, CVD death rates are decreasing steadily both in regions with reliable trend data and globally. The declines in high-income countries and some Latin American countries have been ongoing for decades without slowing. These positive trends have broadly coincided with, and benefited from, declines in smoking and physiological risk factors, such as blood pressure and serum cholesterol levels. These declines have also coincided with, and benefited from, improvements in medical care, including primary prevention, diagnosis, and treatment of acute CVDs, as well as post-hospital care, especially in the past 40 years. These variables, however, explain neither why the decline began when it did, nor the similarities and differences in the start time and rate of the decline between countries and sexes. In Russia and some other former Soviet countries, changes in volume and patterns of alcohol consumption have caused sharp rises in CVD mortality since the early 1990s. An important challenge in reaching firm conclusions about the drivers of these remarkable international trends is the paucity of time-trend data on CVD incidence, risk factors throughout the life-course, and clinical care.